Restoration of Noncarious Cervical Lesions: When, Why, and How - Cesar dos Reis Perez; Mariana Rodrigues Gonzalez; Natália Aráujo Silva Prado; Marianna Sorozini Ferreira de Miranda; Mariana de Andrade Macêdo; Bárbara Monteiro Pessôa Fernandes (International Journal of Dentistry)
At this time, restoration of noncarious cervical lesions (NCCLs) is a common occurrence in clinics nowadays. Some reasons for this are the growth of the elderly population, a smaller rate of tooth loss, and possibly the increase of some etiologic factors. These factors include inadequate brushing techniques in gingival recession cases, corrosive food and drink consumption, and occlusal stress concentrating factors (occlusal interferences, premature contacts, habits of bruxism, and clenching). Unfortunately, Class V restorations also represent one of the less durable types of restorations and have a high index of loss of retention, marginal excess, and secondary caries. Some causes for these problems include difficulties in isolation, insertion, contouring, and finishing and polishing procedures. This work aims to help dentists in choosing the best treatment strategy, which necessarily involves steps of problem identification, diagnosis, etiological factor removal or treatment, and, if necessary, restoration. Finally, appropriate restorative techniques are suggested for each situation.